2021
DOI: 10.4081/aiua.2021.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted segmental ureterectomy with psoas hitch ureteral reimplantation: Oncological, functional and perioperative outcomes of case series of a single centre

Abstract: Introduction: According to the Urology guidelines, in selected cases of distal upper tract urothelial carcinoma (UTUC) segmental ureterectomy (SU) can be offered. There is no consensus in the surgical technique of preference. Robot-assisted SU could be an option to overcome all the limitations of open and laparoscopic techniques. We describe our first experience of robot assisted SU with psoas hitch ureteral reimplantation (RAPHUR). Materials and methods: 11 patients underwent RAPHUR for distal UTUC between 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Over time, minimally invasive approaches are increasingly being utilized with less perioperative complications and faster recovery (24). Lenis et al concluded that compared with open RNU, robot-assisted RNU does not compromise performance of lymph node dissection and may be associated with LN yield (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over time, minimally invasive approaches are increasingly being utilized with less perioperative complications and faster recovery (24). Lenis et al concluded that compared with open RNU, robot-assisted RNU does not compromise performance of lymph node dissection and may be associated with LN yield (25).…”
Section: Discussionmentioning
confidence: 99%
“…Lenis et al. concluded that compared with open RNU, robot-assisted RNU does not compromise performance of lymph node dissection and may be associated with LN yield ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously published our initial experience with robotic-assisted nephron-sparing management of ureteral tumors ( 14 , 15 ) and recently highlighted (in our most updated series), various reconstructive options including an anecdotal case report of utilizing a wedge of ileum to patch a significant defect following SU ( 16 ). Other single and multi-institutional studies have also reported the safety, feasibility and effectiveness of robotic-assisted nephron-sparing management of ureteral tumors ( 17 - 21 ) ( Table 2 ).…”
Section: Alternatives To Rnumentioning
confidence: 99%